Rancangan Sistem Start Engine dan Alarm pada Sepeda Motor Menggunakan Arduino Uno Berbasis Android - Purwanto, Mahfud Ichsan Adi, Aris Rakhmadi, S.T., M.Eng (2017)
Common motorcycles use the conventional keys to secure and start the engine. This study aims to create a Bluetooth remote android application to control a motorcycle bluetooth using android. This system can help the user to start the engine and turn on the alarm motorcycle from a certain distance. Arduino Uno is a main control on motorcycle. This study uses Android mobile as a remote. HC-05 Bluetooth shield receives commands sent from Android devices and forwarded to arduino. This application also helps to determine the location of a motorcycle by turning on the alarm. Keywords: Android, Arduino Uno, engine, Alarm.